Parents' Experiences of Health Care for Their Children With Cerebral Palsy. (August 2015) - Hayles, Emily; Harvey, Desley; Plummer, David; Jones, Anne
Although current health care service delivery approaches for children with cerebral palsy recognize the importance of including parents in the health care of their child, we do not yet understand how parents experience this phenomenon. In this study, we used grounded theory methodology to explore parents' experiences of health care for their children with cerebral palsy living in a regional area of Australia. Our findings indicate that parents experience health care for their child as a cyclical process of "making the most of their body and their life." Important aspects of care include "learning as you go, " "navigating the systems, " "meeting needs through partnership, " "being empowered or disempowered, " and "finding a balance." We suggest modifications to health care service delivery practices that might contribute to improved experiences of health care for this population.